Quantitation of G-cells in fibreoptic biopsy specimens and serum gastrin levels in healthy normal subjects. - Piris, J (1975)
The G-cells of the gastric antrum were accurately quantitated in preparations stained with an immunoperoxidase method. In 15 normal young adults the mean G-cell count per unit area was 200 +/- 15-9. Serum gastrin levels were measured in 12, and all fell within the normal range (mean 59-7 +/- 5-4 pg/ml).